1990
DOI: 10.1172/jci114752
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous synthesis and degradation of rat liver glycogen. An in vivo nuclear magnetic resonance spectroscopic study.

Abstract: Using "3C nuclear magnetic resonance spectroscopic methods we examined in vivo the synthesis of liver glycogen during the infusion of D-11-13Cjglucose and the turnover of labeled glycogen during subsequent infusion of D-11-13Cjglucose. In fasted rats the processes of glycogen synthesis and degradation were observed to occur simultaneously with the rate of synthesis > degradation leading to net glycogen synthesis. In fed rats, incorporation of infused D-[1-_3Cjglucose occurred briskly; however, over 2 h there w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
27
0

Year Published

1993
1993
2004
2004

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(33 citation statements)
references
References 35 publications
6
27
0
Order By: Relevance
“…This evidence is essentially in agreement with previous reports dealing with gluconeogenic processes in bacteria (31,32), animals (33,34), and heterotrophic plant cells (35,36). Accordingly, the newly proposed mechanism of starch biosynthesis, which is compatible with most, if not all, starchdeficient and excess mutant and transgenic plant described to date, assumes that gluconeogenic enzymes, such as plastid phosphoglucomutase and AGP, play a role in synthesizing ADPG from the glucose units that are derived from the starch breakdown (Fig.…”
supporting
confidence: 94%
“…This evidence is essentially in agreement with previous reports dealing with gluconeogenic processes in bacteria (31,32), animals (33,34), and heterotrophic plant cells (35,36). Accordingly, the newly proposed mechanism of starch biosynthesis, which is compatible with most, if not all, starchdeficient and excess mutant and transgenic plant described to date, assumes that gluconeogenic enzymes, such as plastid phosphoglucomutase and AGP, play a role in synthesizing ADPG from the glucose units that are derived from the starch breakdown (Fig.…”
supporting
confidence: 94%
“…USA 95 (1998) by mass isotopomer) appears to cycle through the glycogen pool prior to efflux from human liver (43). NMR data also corroborate that significant hepatic glucose-glycogen cycling occurs in vivo (44,45). These data support the conjecture that glycogenolysis inhibition could also reduce net gluconeogenic flux, and thereby contribute to the overall efficacy in reducing HGP in vivo.…”
supporting
confidence: 53%
“…It seems that a compensatory mechanism exists that tends to equilibrate the rates of glycogenolysis and glycogenesis to maintain glycogen turnover and net glycogen content. The simultaneous existence of both reactions or glycogen cycling has been clearly demonstrated in liver (37). Furthermore, in liver, glycogen turnover is greater in the fed state than in the fasted state (38), and thus it has been suggested that glycogen concentration may exert a regulatory effect on glycogen turnover.…”
Section: Resultsmentioning
confidence: 99%